Crescendo [videorecording (DVD)] - Zahavi, Dror, 1959-; Zahavi, Dror, 1959-; Simonischek, Peter; Beglau, Bibiana, 1971-; Donskoy, Daniel, 1990- (Menemsha Films, 2020)
A world-renowned conductor creating an Israeli-Palestinian youth orchestra has to bring together musicians from both sides of the conflict and help them overcome their differences and mutual distrust.